1983
DOI: 10.1116/1.571907
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature oxygen diffusion in alpha titanium characterized by Auger sputter profiling

Abstract: Anodic TiO2 films were grown on titanium foils under galvanostatic conditions at 20 mA/cm2 in an aqueous saturated solution of ammonium tetraborate. The samples were then heat treated at temperatures between 450 and 550 °C and changes in the profile of oxygen concentration as a function of depth were monitored using Auger electron spectroscopy (AES). The oxygen diffusivities were calculated from the Boltzmann–Matano method and compared with those obtained using an analytical solution to Fick’s second law. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The higher the hydrogen concentration, the safer the pyrotechnic materials are. This agrees well with our studies, whic show a hydrogen diffusion before the oxygen diffusion into the fuel; this hydrogen outward diffusion requires additional activation energies for pyrotechnic reaction [13][14][15][16][17][18][19][20].…”
Section: 1 Statistics and Accuracysupporting
confidence: 91%
“…The higher the hydrogen concentration, the safer the pyrotechnic materials are. This agrees well with our studies, whic show a hydrogen diffusion before the oxygen diffusion into the fuel; this hydrogen outward diffusion requires additional activation energies for pyrotechnic reaction [13][14][15][16][17][18][19][20].…”
Section: 1 Statistics and Accuracysupporting
confidence: 91%
“…In addition, using Auger electron spectroscopy, Wittberg at al. have shown that the annealing of TiO 2 films involves a non-homogenous oxygen diffusion process, with higher oxygen concentration at the surface [27]; hence, a different chemical composition along with the film depth was proposed [23,28]. This gradient results in a change in permittivity spectrum so light passing through the nanotubes layer is bent before it is reflected back from the Ti substrate.…”
Section: Anodisation Growth and Timementioning
confidence: 98%
“…The shape of the photospectra for the thermally treated anodic films was similar to that observed for thermal films formed at 400~ in air on bare titanium substrates. The effect of heating on the TiO2/Ti system has been studied by several investigators for nonelectrochemically produced oxide films (29)(30)(31) and also for anodic TiO2 films (32)(33)(34). In general the donor distribution is observed to become nonuniform and an increase in photoresponse is observed after heating in either oxidizing (air, pure oxygen) or reducing (argon, vacuum) atmospheres.…”
Section: Reflection Electron Diffraction--diffraction E X P E R I M E...mentioning
confidence: 99%
“…Upon heating the films in air, oxygen vacancies can be filled, resulting in increased light absorption associated with the electronic transition from the 2p level of 0 _2 to the empty d-state of Ti § (35) and a resulting change in the absorption spectra (29). Heat-treatment of the TiO2/Ti system has also been observed to cause oxygen to diffuse into the titanium substrate producing a more diffuse oxide/metal interface (33). Oxygen incorporation into the film at the oxide/gas interface and oxygen loss at the oxide/metal interface will result in a nonuniform donor distribution, thus altering the depletion layer characteristics and ultimately the photocurrent response.…”
Section: Reflection Electron Diffraction--diffraction E X P E R I M E...mentioning
confidence: 99%